ANALISIS PENGENAANPAJAK PENGHASILAN PASAL 21 ATAS GAJI PEGAWAI TETAP PD. BPR BAHTERAMAS KABUPATEN BUTON - Tasmita, Yuni Nuardi; Isna, Isna (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
: This research is entitled Analysis of the Imposition of Income Tax Article 21 on the salaries of PD employees. BPR Bahteramas Buton. The problem in this study is how the imposition of income tax article 21 on the salaries of PD employees. BPR Bahteramas Buton. This study aims to analyze how the imposition of income tax article 21 on the salaries of PD employees. BPR Bahteramas Buton. The type of data used is quantitative data and qualitative data, while the data collection technique is documentation. The analytical method used is descriptive method, namely compiling, collecting, analyzing data collected in the form of numbers. Based on the results of data analysis, it is concluded that the imposition of Article 21 Income Tax which has been carried out by PD BPR Bahteramas Buton is not in accordance with Law Number 36 of 2008